Familial screening in case of acute myocarditis reveals inherited arrhythmogenic left ventricular cardiomyopathies. (1st May 2020) - Piriou, Nicolas; Marteau, Lara; Kyndt, Florence; Serfaty, Jean Michel; Toquet, Claire; Le Gloan, Laurianne; Warin‐Fresse, Karine; Guijarro, Damien; Le Tourneau, Thierry; Conan, Emilie; Thollet, Aurélie; Probst, Vincent; et al.
Abstract: Aims: Several data suggest that acute myocarditis could be related to genetic variants involved in familial cardiomyopathies, particularly arrhythmogenic cardiomyopathy, but the management of patients with acute myocarditis and their families regarding their risk for having an associated inherited cardiomyopathy is unclear. Methods and results: Families with at least one individual with a documented episode of acute myocarditis and at least one individual with a cardiomyopathy or a history of sudden death were included in the study. Comprehensive pedigree, including genetic testing, and history of these families were analysed. Six families were included. Genetic analysis revealed a variant in desmosomal proteins genes in all the probands [five in desmoplakin (DSP) gene and one in desmoglein 2 gene]. In the five families identified with a DSP variant, genetic testing was triggered by the association of an acute myocarditis with a single case of apparently isolated dilated cardiomyopathy or sudden death. Familial screening identified 28 DSP variant carriers; 39% had an arrhythmogenic left ventricular (LV) cardiomyopathy phenotype. Familial histories of sudden death were frequent, and a remarkable phenotype of isolated LV late gadolinium enhancement on contrast‐enhanced cardiac magnetic resonance without any other structural abnormality was found in 38% of asymptomatic mutation carriers. None of the DSP variant carriers had imaging characteristics of right ventricle involvement meeting current Task Force criteria for arrhythmogenic right ventricular cardiomyopathy. Conclusions: Comprehensive familial screening including genetic testing in case of acute myocarditis associated with a family history of cardiomyopathy or sudden death revealed unknown or misdiagnosed arrhythmogenic variant carriers with left‐dominant phenotypes that frequently evade arrhythmogenic right ventricular cardiomyopathy Task Force criteria. In view of our results, acute myocarditis should be considered as an additional criterion for arrhythmogenic cardiomyopathy, and genetic testing should be advised in patients who experience acute myocarditis and have a family history of cardiomyopathy or sudden death.